Distinct type I interferon responses between younger women and older men contribute to the variability of COVID-19 outcomes: Hypothesis generating insights from COVID-19 convalescent individuals. (September 2022) - Mavragani, Clio P.; Skarlis, Charalampos; Kostopoulos, Ioannis V.; Maratou, Eirini; Moutsatsou, Paraskevi; Terpos, Evangelos; Tsitsilonis, Ourania E.; Dimopoulos, Meletios-Athanasios; Sfikakis, Petros P.
Highlights: Older age and male sex are associated with dismal outcomes among COVID-19 infected patients in epidemiological studies. Higher type I IFN responses and lower IL-6 serum levels were observed in convalescent sera from women of premenopausal age compared to older males. Dampened type I IFN pathway activation and heightened proinflammatory cytokines were previously shown to predict severe COVID-19 outcomes. Taken together, the findings of the current study could explain the variability in COVID-19 outcomes in distinct age and sex groups. Abstract: Background/Objective: Older age and male sex have been consistently found to be associated with dismal outcomes among COVID-19 infected patients. In contrast, premenopausal females present the lowest mortality among adults infected by SARS-CoV-2. The goal of the present study was to investigate whether peripheral blood type I interferon (IFN) signature and interleukin (IL)-6 serum levels -previously shown to contribute to COVID-19-related outcomes in hospitalized patients- is shaped by demographic contributors among COVID-19 convalescent individuals. Patients and Methods: Type I IFN-inducible genes in peripheral blood, as well as serum IL-6 levels were quantified in 61 COVID-19 convalescent healthy individuals (34 females, 27 males; age range 18–70 years, mean 35.7 ± 15.9 years) who recovered from COVID-19 without requiring hospitalization within a median of 3 months prior to inclusion in the present study. Among those, 17 were older than 50 years (11 males, 6 females) and 44 equal to or less than 50 years (16 males, 28 females). Expression analysis of type I IFN-inducible genes (MX-1, IFIT-1, IFI44) was performed by real time PCR and a type I IFN score, reflecting type I IFN peripheral activity, was calculated. IL-6 and C-reactive protein levels were determined by a commercially available ELISA. Results: COVID-19 convalescent individuals older than 50 years exhibited significantly decreased peripheral blood type I IFN scores along with significantly increased IL-6 serum levels compared to their younger counterparts less than 50 years old (5.4 ± 4.3 vs 16.8 ± 24.7, p = 0.02 and 10.6 ± 16.9 vs 2.9 ± 8.0 ng/L, p = 0.03, respectively). Following sex stratification, peripheral blood type I IFN score was found to be significantly higher in younger females compared to both younger and older males (22.9 ± 29.2 vs 6.3 ± 4.6 vs 4.5 ± 3.7, p = 0.01 and p = 0.002, respectively). Regarding IL-6, an opposite pattern was observed, with the highest levels being detected among older males and the lowest levels among younger females (11.6 ± 18.9 vs 2.5 ± 7.8 ng/L, p = 0.03). Conclusion: Constitutive higher type I IFN responses and dampened IL-6 production observed in younger women of premenopausal age, along with lower type I IFN responses and increased IL-6 levels in older males, could account for the discrete clinical outcomes seen in the two population groups, as consistently revealed in COVID-19 epidemiological studies.